Structure-property relationship on aggregation-induced emission properties of simple azine-based AIEgens and its application in metal ions detection - Sun, Xiao-Mei; Liu, Juan; Li, Zhao-Hui; Fu, Yong-Peng; Huang, Ting-Ting; Tang, Zhong-Di; Shi, Bingbing; Yao, Hong; Wei, Tai-Bao; Lin, Qi (Chinese chemical letters, 2023)
In recent twenty years, aggregation-induced emission (AIE), due to its excellent application prospect, has aroused widespread interests. The development of novel and easy to make AIE luminogens (AIEgens) is an attractive subject. For this purpose, it is very important to study the structure-property relationship of AIEgens. Because azine derivatives are easy to synthesis and some of them have nice AIE properties, herein, a series of azine derivatives (ADs) were employed as models to study the influence of different functional groups, electronic effects and structures on the AIE properties of azine derivatives. The AIE mechanism were studied by single crystal analysis, density functional theory (DFT) calculations and so on. The results indicated that the o-hydroxyl aryl substituted azine compounds could show good AIE properties. Meanwhile, the AIE properties of o-hydroxyl aryl substituted azine compounds were also influenced by the electronic effects of the aryl groups in the azine compounds. The o-hydroxyl groups could form intramolecular hydrogen bond with imine group, which play key role to restrict the intramolecular rotation of the aryl groups and act as base stone for the AIE process of this kind compounds. The HOMO-LUMO energy gaps of o-hydroxyl substituted azine are smaller than other homologous compounds, which is agree with the proposed AIE mechanism. Finally, thanks to the AIE properties, the o-hydroxy-substituted azines could be used as efficient Al3+ and Cu2+ fluorescent chemosensors in different conditions. In addition, test strips based on AD10 has been prepared, which can conveniently detect Cu2+ in industrial wastewater. This research supplied a way for the design of novel easy to make AIEgens through simple azine derivatives. The AIE mechanism and structure-property relationship of azine derivatives were studied. The o-hydroxyl aryl substituted azine compounds could show good AIE properties and can act as Al3+ and Cu2+ sensor in different conditions. [Display omitted]